Jefferson Alumni Bulletin – Volume XXVII, Number 4 Summer 1977 (Jefferson Digital Commons, 1977)
Jefferson Alumni Bulletin – Volume XXVII, Number 4 Summer 1977 Profile of a President, Page 2 The “Wise Infidelity” of Vesalius and Pare, Page 13 At First, Only John Gibbon Believed in the Heart-Lung Machine, Page 19 Modernizing Eskimo Health Care, Page 22 Family Practice Relates to People’s Needs, Page 24 Jefferson Scene, Page 26 Class Notes, Page 34 Obituaries, Page 43